(untitled) (BALEAP Journal of Research and Practice, 2025)
In this reflective exploration, we navigate trioethnographic methodology employed to investigate our evolving professional identities and the concept of social justice in English for Academic Purposes (EAP). Our journey, sparked by collaborative writing of a book chapter, emphasized creativity, dialogue, and an ethic of care, resonating deeply with our roles within the EAP for Social Justice Special Interest Group (SIG). We explore the intersections of reflection, trioethnography, and rhizomatic analysis, revealing how these approaches facilitated a profound understanding of our experiences and identities. Blackout poetry emerged as a transformative tool, allowing for alternative interpretations and deeper engagement with our data. Our methodology challenged conventional academic norms, embracing non-linear, interdisciplinary approaches that celebrate multiplicity and inclusivity. Through our research, we address the tensions between traditional academic writing and innovative, transformative narrative styles. The reflective process underscored the significance of trust, vulnerability, and ethical care in collaborative research. Ultimately, our work culminates in a manifesto advocating for creative knowledge-making and collaboration in EAP, urging EAP practitioners and other educators to embrace unconventional narratives and foster inclusive, empathetic learning environments.